Efektivitas Achievement Motivation Training (AMT) Berbasis Islam dalam Meningkatkan Motivasi Menghafal Alquran Santri - Ema Zati Baroroh; Dedi Firmansyah; Nurul Hasanah (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2023)
This study aims to examine the effectiveness of Islamic-based Achievement Motivation Training (AMT) in increasing motivation to memorize the Quran. This study used a quantitative pre-experimental method with a one group pretest-posttest design. The participants were 8 teenage boys aged 11-17 years, who were students at Pondok Tahfizh Quran Hisbah Al-Mizan Pontianak who were selected through random sampling. Data collection used a scale of motivation to memorize the Quran with a value of α .7737. Based on the paired sample of t test, a significance value of .004 (p < .05) was obtained, which indicated that there were differences in the level of motivation to memorize the Quran before and after training. Thus the Islamic-based Achievement Motivation Training (AMT) is effective in increasing the motivation to memorize the Quran in students.